2017
DOI: 10.7181/acfs.2017.18.3.202
|View full text |Cite
|
Sign up to set email alerts
|

Angiomyolipoma of the Glabellar Region

Abstract: Angiomyolipomas are hamartomatous lesions consisting of smooth muscle bundles, thick-walled blood vessels, and mature adipocytes. They are usually found in the kidneys of tuberous sclerosis patients and more rarely in other organs, such as the liver, the oral cavity, the sinonasal tract, the heart, the large intestines, the lungs, and the skin. Cutaneous angiomyolipoma has shown to be very rare and generally occurs at the ends of the digits, the elbows, the ears, and the nose. Herein, we report the first docum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…The sporadic type of AML is the most common (80-90% of cases) and usually develops in older patients. [5][6][7] On extensive review of literature, till date only 36 cases of uterine AML have been reported in the English literature, most of them being single case reports. 1,2 Mulchandani et al reported the only Indian case of uterine AML and did a comprehensive review of 28 cases of uterine AML reported till then.…”
Section: Discussionmentioning
confidence: 99%
“…The sporadic type of AML is the most common (80-90% of cases) and usually develops in older patients. [5][6][7] On extensive review of literature, till date only 36 cases of uterine AML have been reported in the English literature, most of them being single case reports. 1,2 Mulchandani et al reported the only Indian case of uterine AML and did a comprehensive review of 28 cases of uterine AML reported till then.…”
Section: Discussionmentioning
confidence: 99%
“…AML are histologically diagnosed as benign tumours with classical triad of mature thick-walled blood vessel, smooth muscle and mature adipose tissue in different proportion [12]. AML are also one of the most common benign tumors in the kidney [3], and over 33%…”
Section: Discussionmentioning
confidence: 99%